Thermal Behavior, Local-Scale Morphology, and Phase Composition of Spherulites in Melt-Crystallized Poly(Vinylidene Fluoride) Films - Denis V. Anokhin; Dana S. Plieva; Martin Rosenthal; Andrei V. Churakov; Dimitri A. Ivanov (Crystals)
Synchrotron microbeam X-ray diffraction was employed to investigate the local-scale structure and solid-state phase transformation within individual spherulites of poly(vinylidene fluoride) (PVDF). In thin, non-oriented films, PVDF crystallizes into α and γ-phases, forming distinct spherulitic morphologies: large, banded α-spherulites and smaller, irregular “mixed” spherulites dominated by the γ-phase. For samples crystallized at high undercooling (160 °C), the mixed spherulites primarily consisted of the γ-phase, with only a minor fraction of α-lamellae localized at the spherulite boundaries. At higher crystallization temperatures (165 °C), the α-phase was entirely absent from the mixed spherulites. High-temperature annealing induced a phase transformation from the α-phase to the γ-phase, initiating at the interface between α- and γ-spherulites. The transformation propagated radially along the b-axis of the α-spherulite, while its characteristic banded morphology remained intact. Radial scanning with an X-ray microbeam provided spatially resolved mapping of the structural transition within the α-spherulite at the micrometer scale, offering detailed insights into the transformation mechanism and its impact on the spherulitic structure. The fast crystal growth direction remained unaltered during the transition, suggesting minimal material transport and maintaining structural coherence.